Establishing high-accuracy biomarkers for colorectal cancer by comparing fecal microbiomes in patients with healthy families. (3rd July 2020) - Yang, Jian; Li, Dongfang; Yang, Zhenyu; Dai, Wenkui; Feng, Xin; Liu, Yanhong; Jiang, Yiqi; Li, Pingang; Li, Yinhu; Tang, Bo; Zhou, Qian; Qiu, Chuangzhao; et al.
ABSTRACT: Colorectal cancer (CRC) causes high morbidity and mortality worldwide, and noninvasive gut microbiome (GM) biomarkers are promising for early CRC diagnosis. However, the GM varies significantly based on ethnicity, diet and living environment, suggesting varied GM biomarker performance in different regions. We performed a metagenomic association analysis on stools from 52 patients and 55 corresponding healthy family members who lived together to identify GM biomarkers for CRC in Chongqing, China. The GM of patients differed significantly from that of healthy controls. A total of 22 microbial genes were included as screening biomarkers with high accuracy in additional 46 cases and 40 randomly selected healthy adults in Chongqing (area under the receive-operation curve (AUC) = 0.905, 95% CI 0.832–0.977). The classifier based on the identified 22 biomarkers also performed well in the cohort from Hong Kong (AUC = 0.811, 95% CI 0.715–0.907) and French (AUC = 0.859, 95% CI 0.773–0.944) populations. Quantitative PCR was applied for measuring three selected biomarkers in the classification of CRC patients in independent Chongqing population containing 30 cases and 30 controls and the best biomarker from Coprobacillus performed well with high AUC (0.930, 95% CI 0.904–0.955). This study revealed increased sensitivity and applicability of our GM biomarkers compared with previous biomarkers significantly promoting the early diagnosis of CRC.